Implementacion de un sistema de intercambio de calor de placas paralelas para su uso como recursos didactico en el laboratorio de transferencia de calor (2022)
This document presents the conceptual design and detailed manufacturing of a plate heat exchanger, which will be implemented in the experiences of the laboratory, corresponding to the area of ​​heat transfer, by the students of the University Antonio Narino